A guide to wildlife friendly tourism by the members of Visit Rupununi - Food and Agriculture Organization of the United Nations; Center for International Forestry Research; Centre de coopération internationale en recherche agronomique pour le développement; WCS (Food and Agriculture Organization of the United Nations, 2022)
The Sustainable Wildlife Management (SWM) Programme in Guyana is encouraging coordinated community-driven initiatives that support food security and traditional livelihoods. These will contribute to maintaining healthy fish and terrestrial wildlife populations. It is being implemented by the Guyana Wildlife Conservation and Management Commission in coordination with the Center for International Forestry Research (CIFOR).